2016
DOI: 10.1128/aac.01907-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparative RNA-seq-Based Transcriptome Analysis of the Virulence Characteristics of Methicillin-Resistant and -Susceptible Staphylococcus pseudintermedius Strains Isolated from Small Animals

Abstract: Staphylococcus pseudintermedius is often associated with pyoderma, which can turn into a life-threatening disease. The dissemination of highly resistant isolates has occurred in the last 10 years and has challenged antimicrobial treatment of these infections considerably. We have compared the carriage of virulence genes and biofilm formation between methicillin-resistant and methicillin-susceptible S. pseudintermedius (MRSP and MSSP, respectively) isolates and their in vitro gene expression profiles by transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
3
13
1
1
Order By: Relevance
“…N, number of isolates; ST45_1, ST45 sublineage 1; ST45_2, ST45 sublineage 2. core virulence genes, however, can vary in different lineages, leading to lineage-wise differences in pathogenicity. The levels of expression of virulence genes are just as important as their lineage-specific presence (22). The frequencies of the remaining 17 virulence-associated genes varied across lineages, and they formed the basis of our virulence gene content analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…N, number of isolates; ST45_1, ST45 sublineage 1; ST45_2, ST45 sublineage 2. core virulence genes, however, can vary in different lineages, leading to lineage-wise differences in pathogenicity. The levels of expression of virulence genes are just as important as their lineage-specific presence (22). The frequencies of the remaining 17 virulence-associated genes varied across lineages, and they formed the basis of our virulence gene content analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We compiled a list of 69 virulence-associated genes from S. pseudintermedius and other Staphylococcus species (Table S2). This included genes involved in host adaptation, attachment and invasion, host cell lysis, immune evasion, biofilm formation, and regulation of the expression of genes involved in virulence (17,21,22,26,31,32,34,55,(60)(61)(62). The presence of these genes in the genome assemblies of 622 strains was determined using large-scale BLAST score ratio (LS-BSR) with the blastn option (63).…”
Section: Methodsmentioning
confidence: 99%
“…scription of some bacterial pathogens could be informative of their virulence level. For example, transcriptional profiling of methicillin-resistant and -susceptible cultures of Staphylococcus pseudintermedius identified differentially expressed genes such as surface proteins, toxins, and prophage genes that might contribute to virulence (42). In the current study, we produced a comprehensive transcriptome data set from which basal transcription patterns were analyzed in multiple aspects putatively associated with virulence potential.…”
Section: Figmentioning
confidence: 99%
“…Importantly, several studies reported differential expression of conserved genes between pathogenic versus nonpathogenic isolates (40)(41)(42)(43) which could reflect the contribution of the regulatory network to fine-tuning gene expression of virulent isolates immediately after ingestion and in the gastrointestinal tract, therefore maximizing their fitness in the host system (44). However, as most studies were restricted to a limited number of strains, the weight of intraspecific diversity tended to be overlooked.…”
mentioning
confidence: 99%
“…Comparisons have also been made between Methicillin-susceptible (MSSP) and Methicillin-resistant S. pseudintermedius (MRSP) in order to determine if their virulence factor profiles are different. In another study (Couto et al 2016), twenty one MRSP and twenty one MSSP, obtained from 18 asymptomatic carriers and 24 diseased dogs and cats were included. MRSP seemed to upregulate surface proteins, increasing the adherence of isolates to keratinocytes.…”
Section: Staphylococcus Intermedius Groupmentioning
confidence: 99%